Patients value climate change counseling provided by their pediatrician: The experience in one Wisconsin pediatric clinic - Andrew A Lewandowski; Perry E Sheffield; Samantha Ahdoot; Edward W Maibach (Elsevier, 2021)
In 2015, the American Academy of Pediatrics (AAP) recommended that the health effects of climate change be incorporated into the existing anticipatory guidance framework. Despite this recommendation, there are only anecdotal accounts of pediatricians offering climate change counseling, and no literature evaluates such counseling effectiveness in any outpatient setting. This investigation describes patient and family responses to climate change counseling administered by one pediatrician in a Wisconsin clinic. A standardized message about the effects of climate change on children's health was delivered during 262 well-child encounters (234 unique families) over a 3 month period. Electronic surveys were administered (response rate of 59% (138/234)) to evaluate knowledge gained as a result of the counseling, intentions of respondents to change their energy use behaviors, and degree of support for clean energy initiatives. Self-described political ideology and general responses to the counseling were also collected. Large majorities of liberal, moderate and conservative families responded positively to the guidance. Although limited to the patients of one pediatrician in a single pediatric practice, our findings bolster the AAP recommendation that counseling about climate change as a child health issue in the outpatient setting is an important and potentially effective educational strategy.